Untangling the Physio-Chemical and Transcriptional Changes of Black Gram Cultivars After Infection With Urdbean Leaf Crinkle Virus - Karthikeyan, Adhimoolam; Akilan, Manoharan; Samyuktha, Santhi Mathavan; Ariharasutharsan, Gunasekaran; Shobhana, V. G.; Veni, Kannan; Tamilzharasi, Murugesan; Keerthivarman, Krishnan; Sudha, Manickam; Pandiyan, Muthaiyan; Senthil, Natesan (Frontiers in Sustainable Food Systems, 2022)
Black gram (Vigna mungo) is an important pulse crop of India. The leaf crinkle disease caused by the urdbean leaf crinkle virus (ULCV), is a severe threat to black gram production. Black gram plants infected by ULCV show a considerable decline in plant growth and yield. However, detailed information about the interactions between the host, black gram, and ULCV is unclear. This study investigated the responses of two cultivars VBN (Bg) 6 and CO 5 to ULCV infection by physiological, biochemical, and transcriptional analyses. Virus symptoms were mild in VBN (Bg) 6 but were serious in CO 5. Upon the viral infection, VBN (Bg) 6 exhibited a low reduction in chlorophyll content than CO 5. The levels of sugar, protein, phenol, hydrogen peroxide (H2O2), and malondialdehyde (MDA) contents were altered by viral infection in both cultivars. Although, the activities of antioxidant enzymes [Ascorbate peroxidase (APX), and superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT)] were increased by ULCV infection. Following the viral infection, the expression level of the salicylic acid (SA), jasmonic acid (JA), and ethylene (ET) defense pathway-related genes was recorded higher in the VBN (Bg) 6 than that recorded in CO 5, indicating a positive correlation between resistance and these indicative indices. This dynamic physio-biochemical and transcriptional profiles of two black gram cultivars on ULCV infection augment our understanding of the complex interaction response between this crop and its pathogen. Additionally, it offers an inventory of potential indicators for future black gram screening and breeding to enhance resistance.